Answer:
Here's a quick sketch of how to calculate the distance from a point P=(x1,y1,z1)
P
=
(
x
1
,
y
1
,
z
1
)
to a plane determined by normal vector N=(A,B,C)
N
=
(
A
,
B
,
C
)
and point Q=(x0,y0,z0)
Q
=
(
x
0
,
y
0
,
z
0
)
. The equation for the plane determined by N
N
and Q
Q
is A(x−x0)+B(y−y0)+C(z−z0)=0
A
(
x
−
x
0
)
+
B
(
y
−
y
0
)
+
C
(
z
−
z
0
)
=
0
, which we could write as Ax+By+Cz+D=0
A
x
+
B
y
+
C
z
+
D
=
0
, where D=−Ax0−By0−Cz0
D
=
−
A
x
0
−
B
y
0
−
C
z
0
.
This applet demonstrates the setup of the problem and the method we will use to derive a formula for the distance from the plane to the point P
P
.
Step-by-step explanation:
Answer:
yes
Step-by-step explanation:
maybe
<h2><u>
PLEASE MARK BRAINLIEST!</u></h2>
Answer:
D. [16 - 10]
Step-by-step explanation:
The difference between Mari and Saleh is 6 years. 16 - 10 is 6 years, so D. is your answer!
I hope this helps!
- sincerelynini
Answer:
A) measure angle (ACB) with a protractor to ensure it measures 88 degrees
Answer: Choice B) Distributive property
The 4 is distributed through the parenthesis
The outer term 4 is multiplied by each of the inner terms (x and -6)
4 times x = 4x
4 times -6 = -24
those results are then added up
So that's how 4(x-6) turns into 4x-24